Commodification Model of Media Da’wah on Youtube Channel Yuk Ngaji TV - Rohman, Angga Nur; Arif, Mochammad Choirul; Zuhriyah, Luluk Fikri (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
This study describes the forms of commodification in da'wah activities on YouTube media. A YouTube channel called Yuk Ngaji TV has a commodification model for its da'wah activities in the media. The target of da'wah to teenagers, with a variety of interesting and unique content so as to produce various benefits for Yuk Ngaji TV.Â This study aims to analyze how the forms of commodification on YouTube media Yuk Ngaji TV. The research method used is descriptive qualitative with a semiotic theory approach and media political economy. Data collection through documentation and observation. The results of this study prove that there are various forms of commodification that occur in Yuk Ngaji TV's da'wah activities to gain ideological and materialist benefits. Based on the theory of media political economy, there are various forms of commodification carried out, including the content, audience and labor of the Yuk Ngaji TV channel and its religious values. The commodification of the media has implications for the purity of da'wah that must be done properly and correctly, not just used to gain material and ideological benefits for a group. The implications of this research can have positive and negative impacts. The negative impact of the commodification of da'wah causes the fading of the purpose of da'wah rahmatan lil alamin because it focuses on increasing material benefits. While the positive impact on the perpetrators of da'wah is the motivation to create a way of da'wah that is valuable and attractive to da'wah partners.